2002
DOI: 10.1080/10242690210968
|View full text |Cite
|
Sign up to set email alerts
|

Budgetary Trade-Offs Between Defense, Education and Health Expenditures: The Case of Turkey

Abstract: The main objective of this paper is to evaluate empirically the existence of a budgetary trade-off between military, education and health expenditures in Turkey for the time period 1925-1998. Development economists, peace and defense economists and political economists have extensively investigated the existence of a trade-off between military, education and health spending since the 1970s. However, the literature review reveals that it is hard to establish a general theory of budgetary trade-off between milit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…Additionally, different econometric modelling and estimation techniques used by researchers can generate different results for the same data (Deger and Smith, 1983;Ozsoy, 2002;Yildirim and Sezgin, 2002). These differences in research results led to two different strands of thought in the literature.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, different econometric modelling and estimation techniques used by researchers can generate different results for the same data (Deger and Smith, 1983;Ozsoy, 2002;Yildirim and Sezgin, 2002). These differences in research results led to two different strands of thought in the literature.…”
Section: Introductionmentioning
confidence: 98%
“…In the literature related to Turkey, we can see that Ozsoy (2002) found a positive relationship between education-health expenditures and per capita gross national product (GNP), and a trade-off between defence expenditures and education-health expenditures, using a simple OLS model. Using the SUR estimation method in a multi-equation framework, Yildirim and Sezgin (2002) found that there was a trade-off between defence and health expenditures, but a positive relationship between defence and education expenditures.…”
mentioning
confidence: 96%
“…The study on "guns versus butter" dates back to the pioneering work of Russett [12], which revealed that military spending is negatively correlated with the expenditures for health, education and other social welfare programs in the US, the UK, France and Canada. The negative relationship supported by the crowding-out theory has been confirmed in several studies since then [7][8][9][10][11]16]. Peroff [16] and Peroff and Podolak-Warren [11] found the existence of crowding-out effect in the US.…”
Section: Empirical Analysismentioning
confidence: 53%
“…Dabelko and McCormick [8], Deger [9] and Apostolakis [7] added to this view by providing the evidence in 77 countries, 50 less developed countries and 19 Latin American countries, respectively. There was also shown to be a crowding-out effect between defense and social welfare expenditures in Turkey [10]. In contrast, some studies suggested that the increase in defense expenditure could promote social welfare supported by the Keynesian theory [3,4,6,17,18].…”
Section: Empirical Analysismentioning
confidence: 99%
See 1 more Smart Citation